National report on the status of women in Jamaica (Jamaica National Preparatory Commission [Kingston]JM, 1994)
Reviews and appraises the status of women at the national and international level. Looks at future strategic goals and objectives and coresponding financial arrangements.
bibliography: p. 111-118. Prepared for the Fourth World Conference on Women, Beijing, China, September 1995.